Development of therapeutic agents handbook - Gad, Shayne C., 1948- (John Wiley & Sons, 2012)
A comprehensive look at current drug discovery and development methods-and the roadmap for the future Providing both understanding and guidance in characterizing potential drugs and their production and synthesis, Development of Therapeutic Agents Handbook gives professionals a basic tool to facilitate research and development within this challenging process. This comprehensive text brings together, in one resource, a compendium of concepts, approaches, methodologies, and limitations that need to be considered in the formulation of therapeutic agents across a range of therapeutic fields. Both.